Prevalence and causes of Stillbirths at a Tertiary Care Hospital - Huma Habib, Aneela Siddiqui, Mustajab Begum, Mona Kanwal Naz, Abid Rafique Chaudhry, Attaullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Stillbirth is a major obstetrical complication and devastating experience for parents as well as obstetricians. Identification of causes of stillbirth will be helpful in counseling of parents as wellas formulating preventive measures. The Purpose of the current study was to identify the prevalence, causes ofstillbirth and associated complications to suggest preventive measures. This study was carried out from July 2019 to June 2020 at ateaching tertiary care hospital. The Total number of birth during the study period was 6587 and total number of stillbirth was 109,hence prevalence of stillbirth was 16.5 per 1000 total births. Majority of patients 41(37.6%) belongedto maternal age group of 20-24 years of age. Majority of patients 73(67%) were multigravida.Majority72(66.0%) were emergency admissions. Majority of stillbirth 88(80.7%) were preterm, less than 37weeksof gestational age. Majority of stillbirth 49(44.9%) were weighted from 1000-1499gram. Majority ofstillbirth 65(59.6%) were male. Vaginal delivery occurred in 93(85.3%) and 16(14.7%) required surgical intervention. In 21(19.2%) no identifiable cause of stillbirth was found whereas causes identified in88(80.8%). Stillbirth occurred in 27(24.8%) cases of hypertensive disorder of pregnancy and 24(22%)patients of anaemia. Other causes of stillbirth were Abruption 9(8.2%), IUGR 9(8.2%), oligohydramnios 5(4.6%) congenital malformation 3(2.8%), fever 3(2.7%), placenta previa 3(2.8%), gestational diabetes2(1.9%), hypothyroidism 2(1.9%) and uterine rupture in 1(0.9%). DIC occurred in 4(3.6%).TheMajority of patients were unregistered and had not taken antenatal care or had inadequateantenatal care. Hypertensive disorders during pregnancy were the leading cause for stillbirth followed byanemia and unexplained causes. A significant proportion of stillbirths can be prevented by health educationregarding importance of adequate antenatal care, warning signs and institutional deliveries. Emotionalsupport and counseling of patients and her relatives are very much essential in patients having stillbirth.